Kebutuhan Air Bersih Pengunjung Pada Gedung Hotel The Zuri Pekanbaru - Ayu Juwita Piani; Jecky Asmura; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Clean water is very important for life and to meet daily needs. in hotel buildings to carry out activities also need water, including for bathing, cooking, washing, and so on. The water needed for visitors to the hotel is around 246.984 liters/day. Keywords: Clean water